Potassium (K) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Citrus fruits remove large amounts of K compared to other nutrients. Potassium moves from leaves to fruit and seeds as they develop. Potassium is necessary for several basic physiological functions such as the formation of sugars and starch, synthesis of proteins, normal cell division and growth, and neutralization of organic acids. Potassium is important in fruit formation and enhances fruit size, flavor, and color. This nutrient also helps to reduce the influence that adverse weather conditions (such as drought, cold, and flooding) have on citrus trees. This 4-page fact sheet was written by Mongi Zekri and Tom Obreza and published by the UF Department of Soil and Water Science, July 2013.